2020
DOI: 10.3390/ani10030541
|View full text |Cite
|
Sign up to set email alerts
|

Cats Have Increased Protein Digestibility as Compared to Dogs and Improve Their Ability to Absorb Protein as Dietary Protein Intake Shifts from Animal to Plant Sources

Abstract: This retrospective study used 226 dogs and 296 cats to evaluate whether protein absorption was influenced by species, and within species, what influence increasing the percentage of total dietary protein, as plant protein, had on protein absorption. Each food was evaluated by at least one study with a minimum of six dogs or cats assigned to each study. Dietary inclusion of animal and plant based protein was calculated by analysis of ingredients and dietary inclusion level. Both dogs and cats were able to diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…Another factor that could influence protein digestibility is dietary fiber content [55]. In the current study, although crude fiber content in the BSFL meal-based diet was two times more than the level in the PM-based diet (39.5 vs. 14.7 g/kg DM), this had no effect on protein digestibility.…”
Section: Nutrient Digestibilitycontrasting
confidence: 69%
See 1 more Smart Citation
“…Another factor that could influence protein digestibility is dietary fiber content [55]. In the current study, although crude fiber content in the BSFL meal-based diet was two times more than the level in the PM-based diet (39.5 vs. 14.7 g/kg DM), this had no effect on protein digestibility.…”
Section: Nutrient Digestibilitycontrasting
confidence: 69%
“…Digestibility of crude protein decreased as total dietary fiber consumption increased in dogs [57]. The microbiome can both trap nitrogen as bacterial protein and liberate nitrogen as ammonia, therefore, fermentable carbohydrates may influence protein digestibility through lower tract metabolism [55]. Thus, in our study, certain effects on protein digestibility due to crude fiber content can be excluded or rather neglected because of the low contents and/or differences.…”
Section: Nutrient Digestibilitymentioning
confidence: 79%
“…Formulations and proximate analysis were carried out as previously described [10]. All foods were in dry form, and true and apparent digestibility assays were performed as previously described [46].…”
Section: Study Foodsmentioning
confidence: 99%
“…However, there is no recommendation for the percent of protein, which should come from plants or animals [ 36 ]. Although protein adequacy requires the correct amino acids to be absorbed in their appropriate concentrations, the protein digestibility is a valuable indicator of protein nutrition [ 37 ]. In the current study, crude protein digestibility was similar for the meat-based diet and vegetarian diet.…”
Section: Discussionmentioning
confidence: 99%
“…From another point of view, wheat gluten is a highly digestible protein source with an apparent digestibility of 93.8% [ 41 ]. Similarly, inclusion of rice protein concentrate, corn gluten meal, soybean meal, and soybean protein isolate did not negatively influence protein digestibility compared to animal proteins in the canine diets [ 37 ]. Nevertheless, Bednar et al [ 33 ] found that the crude protein digestibility of the plant-based diet (containing soybean meal) was significantly lower (82.7%) compared to dogs fed poultry meal-based diet (87.5%).…”
Section: Discussionmentioning
confidence: 99%